2006
DOI: 10.1111/j.1742-6723.2006.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and management of aural foreign bodies in two Australian emergency departments

Abstract: Aural foreign bodies are a frequent presentation to the ED. Recognition of patients requiring early specialist referral is important. Adults present with a different profile of aural foreign objects to children and require different management. The use of cotton tips or cotton wool in the external ear canal and silicone ear plugs should be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 13 publications
(35 reference statements)
1
31
1
4
Order By: Relevance
“…There were wide variations International Journal of Otolaryngology regarding the type of the aural FB; in Chai et al study, seeds or nuts were the commonest ear FB encountered which consisted of 226 (47.1%) cases; this was followed by plastic toys or beads [12]. In Ologe et al study grains and seeds (27.9%), beads (19.7%), cotton wool (13.6%), paper (8.8%), and eraser (8.2%) formed the bulk of the aural FB [14], but this differed from our results in which beads and cotton tips were common as compared to seeds; this was consistent with other studies [15]. In our study, garlic was encountered as an animate FB because it was used traditionally for the relief of earache.…”
Section: Discussioncontrasting
confidence: 57%
“…There were wide variations International Journal of Otolaryngology regarding the type of the aural FB; in Chai et al study, seeds or nuts were the commonest ear FB encountered which consisted of 226 (47.1%) cases; this was followed by plastic toys or beads [12]. In Ologe et al study grains and seeds (27.9%), beads (19.7%), cotton wool (13.6%), paper (8.8%), and eraser (8.2%) formed the bulk of the aural FB [14], but this differed from our results in which beads and cotton tips were common as compared to seeds; this was consistent with other studies [15]. In our study, garlic was encountered as an animate FB because it was used traditionally for the relief of earache.…”
Section: Discussioncontrasting
confidence: 57%
“…The cotton buds at the end of cotton-tipped applicators may separate, requiring removal as a foreign body. 92 One case report did report fatal otogenic meningitis and brain abscess due to retained cotton swabs. 94 In a prospective study, Lee et al showed that complications do arise from self-cleaning of the external auditory canal.…”
Section: Interventions Not Recommended To Treat Cerumen Impactionmentioning
confidence: 99%
“…92 Removing cerumen with an oral jet irrigator was described by Larsen. 93 Flared tip and OtoClear Tip are promoted as safer tips to eliminate overinsertion and direct the water away from the tympanic membrane, theoretically avoiding the risk of injury by reducing the buildup of pressure causing damage or pain.…”
Section: Interventions Not Recommended To Treat Cerumen Impactionmentioning
confidence: 99%
“…Q-tip use is mostly associated with external otitis and retained foreign bodies than tympanic membrane perforation 6,7 . In a primary care population, 36% of respondents to a survey admitted to cleaning their ears by placing a foreign body in the canal at least one time per day.…”
Section: Introductionmentioning
confidence: 99%